The North Equatorial Current and rapid intensification of super typhoons - Sok Kuh Kang; Sung-Hun Kim; I.-I. Lin; Young-Hyang Park; Yumi Choi; Isaac Ginis; Joseph Cione; Ji Yun Shin; Eun Jin Kim; Kyeong Ok Kim; Hyoun Woo Kang; Jae-Hyoung Park; et al. (Nature Communications, 2024)
Abstract Super Typhoon Mangkhut, which traversed the North Equatorial Current (NEC; 8–17 °N) in the western North Pacific in 2018, was the most intense Category-5 tropical cyclone (TC) with the longest duration in history—3.5 days. Here we show that the combination of two factors—high ocean heat content (OHC) and increased stratification — makes the NEC region the most favored area for a rapid intensification (RI) of super typhoons, instead of the Eddy Rich Zone (17–25 °N), which was considered the most relevant for RI occurrence. The high OHC results from a northward deepening thermocline in geostrophic balance with the westward-flowing NEC. The stratification is derived from precipitation associated with the Inter-Tropical Convergence Zone in the summer peak typhoon season. These factors, which are increasingly significant over the past four decades, impede the TC-induced sea surface cooling, thus enhancing RI of TCs and simultaneously maintaining super typhoons over the NEC region.